Perjuangan Tokoh dalam Novel “Ibu Ketika Surga itu Harus Pergi” Karya Utami Panca Dewi (Analisis Sosiologi Sastra) - Anastasia Ria Indrasworo; Masrin Masrin (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2022)
The research objectives are 1) To describe the elements of the characters, characterizations, settings, and plots that shape the struggles of the characters in the novel "Ibu Ketika Surga Itu Harus Pergi" by Utami Panca Dewi. 2) Describe the struggles of the characters in the novel "Ibu Ketika Surga Itu Harus Pergi " by Utami Panca Dewi. 3) Describe the implementation of the results of the struggles of the characters in the novel " Ibu Ketika Surga Itu Harus Pergi " by Utami Panca Dewi in learning literature in Junior High School. The research used is qualitative research, namely finding something useful based on existing facts, by producing descriptive data. The method used in this research is the sociology of literature method. The conclusions obtained from the research of the dominant struggle are the values of patience and unyielding spirit. For the analysis of the sociology of literature there are aspects of beauty, history, and sociology. In addition, the relationship between the author and society is also influential in the sociology of literature research. Social background, ideology, and social integrity influence authors in making novels. The relationship with the community in the story shows that the sense of social, familial, empathetic, and caring is still very high.